Viral Ventilator-Associated Pneumonia/Hospital-Acquired Pneumonia - Luyt, Charles-Edouard; Hékimian, Guillaume; Bréchot, Nicolas; Chastre, Jean (Seminars in Respiratory and Critical Care Medicine, 2022)
Among the viruses possibly responsible for hospital-acquired and ventilator-associated pneumonia, herpes simplex virus (HSV) is probably the most often involved: HSV reactivation is frequent in intensive care unit patients, and lung parenchymal infection (HSV bronchopneumonitis) has been well described, either using cytological signs of parenchymal involvement in cells obtained during bronchoalveolar lavage or using HSV virus load in the lower respiratory tract. Although treating patients with HSV bronchopneumonitis may be recommended, based on expert opinion, prophylactic or preemptive treatment of HSV reactivation should be avoided. Ventilator-associated pneumonia due to cytomegalovirus (CMV) is less frequent than HSV bronchopneumonitis, and more difficult to diagnose. No data exists on the impact of antiviral treatment on CMV pneumonia. The involvement of respiratory viruses has been described in patients with healthcare-associated pneumonia and hospital-acquired pneumonia, but their role in ventilator-associated pneumonia is not clear.
Keywords: viral infection; herpes simplex virus; cytomegalovirus; respiratory viruses; mechanical ventilation